Black Objects in Supergravity Proceedings of the INFN-Laboratori Nazionali di Frascati School 2011 - Bellucci, Stefano; SpringerLink (Online service) (Heidelberg : Springer International Publishing : Imprint: Springer, 2013)
This is the sixth volume in a series of books on the general topics of supersymmetry, supergravity, black holes and the attractor mechanism. The present volume is based upon lectures held in May 2011 at the INFN-Laboratori Nazionali di Frascati School on Black Objects in Supergravity (BOSS2011), directed by Stefano Bellucci, with the participation of prestigious lecturers, including G. Lopes Cardoso, W. Chemissany, T. Ortin, J. Perz, O. Vaughan, D. Turton, L. Lusanna and S. Ferrara. All lectures were at a pedagogical, introductory level, a feature which is reflected in the specific "flavor" of this volume, which also benefited greatly from extensive discussions and related reworking of the various contributions.
Non-Holomorphic Deformations of Special Geometry and Their Applications -- Black Holes in String Theory -- From Black Strings to Lifshitz Black Branes -- Non-Extremal Black-Hole Solutions of N=2, d=4,5 Supergravity -- Non-Supersymmetric Extremal Black Holes: First-Order Flows and Stabilization Equations -- Non-extremal Black Holes From the Generalised R-Map -- Black Hole Microstate Geometries From String Amplitudes -- From Clock Synchronization to Dark Matter as a Relativistic Inertial Effect -- On Symmetries of Extremal Black Holes With One and Two Centers.
Keywords: Physics; Mathematical physics; Physics; Classical and Quantum Gravitation, Relativity Theory; Mathematical Physics; Mathematical Methods in Physics